2009
DOI: 10.1007/s11104-009-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drought and increasing temperatures on soil CO2 emissions in a Mediterranean shrubland (gariga)

Abstract: In arid and semiarid shrubland ecosystems of the Mediterranean basin, soil moisture is a key factor controlling biogeochemical cycles and the release of CO 2 via soil respiration. This is influenced by increasing temperatures. We manipulated the microclimate in a Mediterranean shrubland to increase the soil and air night-time temperatures and to reduce water input from precipitation. The objective was to analyze the extent to which higher temperatures and a drier climate influence soil CO 2 emissions in the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 61 publications
8
23
2
1
Order By: Relevance
“…This difference was attributable to the concurrent reversed sign of the correlation SR-SWC, confirming the stronger role of SWC than the solely temperature in regulating SR in dry ecosystems subjected to drought. These results are in line with the most recent outcomes on SR modelling in ecosystems facing drought, pointing to include soil moisture, inversely related to soil temperature [53][54][55].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This difference was attributable to the concurrent reversed sign of the correlation SR-SWC, confirming the stronger role of SWC than the solely temperature in regulating SR in dry ecosystems subjected to drought. These results are in line with the most recent outcomes on SR modelling in ecosystems facing drought, pointing to include soil moisture, inversely related to soil temperature [53][54][55].…”
Section: Discussionsupporting
confidence: 91%
“…In WDS, the dry period corresponded with the lower Q 10 , reflecting the low bacterial activity in this site reported by [65]. For SDS, the dry period corresponded to the higher Q 10 , as was already observed by de Dato et al [53]. Davidson and Janssens [66] reported that the decomposition of more complex substrates could likely lead to higher Q 10 .…”
Section: Discussionsupporting
confidence: 71%
“…The relatively moderate rain exclusion applied in our study that resulted in a 6.5 % lower soil water content on average in rain-excluded plots compared to the control plots might not have been strong enough to affect the functioning of the soil microbial communities more clearly and more consistently over the 2 years of our experiment. On the other hand, previous studies applying more severe treatments of rain exclusion and evaluating the effect on soil processes in Mediterranean ecosystems also reported weak or no effects (Sardans et al 2006;de Dato et al 2010;Pailler et al 2014). For example, de Dato et al (2010) applied a total rain exclusion during spring and autumn in a semiarid Mediterranean shrubland and reported decreased soil CO 2 emissions for only three of ten occasions in rain-excluded plots compared to control plots after 5 years of climate manipulation.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, previous studies applying more severe treatments of rain exclusion and evaluating the effect on soil processes in Mediterranean ecosystems also reported weak or no effects (Sardans et al 2006;de Dato et al 2010;Pailler et al 2014). For example, de Dato et al (2010) applied a total rain exclusion during spring and autumn in a semiarid Mediterranean shrubland and reported decreased soil CO 2 emissions for only three of ten occasions in rain-excluded plots compared to control plots after 5 years of climate manipulation. Pailler et al (2014) showed that a severe heat-drought stress applied on soil samples from a Mediterranean forest (10 days at 50°C) decreased the activity of the soil microbial community but did not affect their catabolic profiles, compared to control conditions.…”
Section: Discussionmentioning
confidence: 96%
“…The soil is rocky and shallow and is covered mostly by a malacophyllous drought semideciduous species: Cistus monspeliensis L. The height of the plants is lower than 1 m. The climate is Mediterranean with a mean annual temperature of 16.8 °C and a mean annual rainfall of 640 mm. Further information on the site characteristics are reported in De Dato et al (2008Dato et al ( , 2010. Six chamber soil collars, delimiting six areas including at least one Cistus plant, were installed about 2 months prior to the start the measurements, in order to allow root re-colonization after the disturbance.…”
Section: Nee Ter Measurements and Gp Estimation In A Mediterranean Gmentioning
confidence: 99%